COVID-2019 – Time to Use Silver Diamine Fluoride for Caries Arrest in General Dental Practice?. (2nd September 2020) - Timms, Laura; Deery, Chris; Stevens, Claire; Rodd, Helen
Abstract : Silver diamine fluoride (SDF) is applied topically to arrest caries and has an increasing evidence base to support its efficacy, both in the primary dentition and to arrest root caries in older patients. It can be used as a non-aerosol generating procedure and is a simple technique. It has a side-effect of discolouring caries black, a factor which requires discussion with patients and their carers prior to application. Due to its efficacy and simplicity, it is a useful intervention for the management of caries. CPD/Clinical Relevance: Caries is a common condition in the UK, and silver diamine fluoride offers a simple alternative management technique when case selection is appropriate.